Tantangan Studi Hukum Islam di Indonesia Dewasa Ini - M. Atho Mudzhar (JURNAL INDO-ISLAMIKA, 2012)
This article offers a method of identifying and examining the challenges facing Islamic law studies in Indonesia today in two steps. Firstly, it argues that the study of Islamic law is more than just the study of fiqh and usul al-fiqh; it includes three broad areas of philosophy, normative studies, and empirical studies, all of which have to be studied congruently and imbalances on any part of which will constitute the challenge itself. Secondly, by classifying and examining the topics of doctoral dissertation submitted to the UIN Syarif Hidayatullah Jakarta in terms of those three areas of studies of Islamic law, it was found that in the last 30 years (1982-2011) out of some 836 dissertations that had been submitted to the university the highest proportion of which was on Islamic law (34, 7 %) and mostly on normative conventional Islamic laws. Very little of those studies were devoted to empirical and philosophical studies of Islamic law, probably because of the lack of familiarity with various fields of social sciences and humanities as the auxiliary sciences to the study of law. This is the challenge that has to be remedied in the future.